Autonomous Robot Path Planning in Static and Dynamic Environment by Applying Nature Inspired Computing (NIC) Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The mobile robot path planning is a central problem in several areas such as modern industry and cyber physical systems. This requires an embedding intelligence into that robotics for ensuring feasible solutions to task execution. Most of Research Problems are solved by observing the nature to solve our real-life day-to-day problems. The logic behind computing algorithms is inspired by nature for solving idea of computations problems. These algorithms are best optimization problems to solve computational problems in a reasonable time and providing optimum results. Path planning is one of the tasks of mobile robot to reach towards destination without any disturbance for reaching their goal within time bound.  In this paper, the particle swarm optimization (PSO) is applied for mobile robot path planning to reach its destination. The performance results of proposed PSO for mobile robot path planning shows better results with conventional algorithms to reach destination with minimum energy consumption and also with minimize efficiency towards travelling from source to destination path.